Second-Line Treatment of NSCLC—The Pan-ErbB Inhibitor Afatinib in Times of Shifting Paradigms - Köhler, Jens (Frontiers in Medicine, 2017)
In contrast to the established role of epidermal growth factor receptor (EGFR) inhibitors for the first-line treatment of patients with non-small cell lung cancer (NSCLC) harboring activating EGFR mutations, the role of EGFR blockade and of EGFR molecular testing in the second-line treatment remains less clear. The irreversible pan-ErbB family inhibitor afatinib (Gi(l)otrif®) was recently FDA- and EMA-approved for the second-line treatment of NSCLC with squamous cell histology irrespective of the EGFR mutational status (LUX-Lung 8). Contrariwise, results from the TAILOR and DELTA trials among retrospective biomarker analyses show the predictive value of the EGFR mutational status for efficacy of reversible EGFR inhibitors also as a second-line therapy. This mini review critically summarizes the current role of EGFR targeting strategies in the second-line treatment of NSCLC with special respect to afatinib in light of emerging T790M-specific EGFR and immune check point inhibitors. The review also emphasizes the urgent need for reliable biomarkers to guide therapeutic decision making and outlines prospective changes to the second-line landscape with some of the current second-line treatment concepts likely to be moved to the first-line.